2018
DOI: 10.1016/j.srhc.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Early breastfeeding problems: A mixed method study of mothers’ experiences

Abstract: Breastfeeding problems occurred frequently in the early postnatal period and often caused breastfeeding to be painful. Health care professionals should prepare mothers to deal with possible breastfeeding problems. New support options should be reviewed in an early postnatal discharge setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
59
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 21 publications
(27 reference statements)
10
59
0
8
Order By: Relevance
“…Primiparous women are more likely to experience pain during breastfeeding than multiparous women is perhaps not a surprising result, nevertheless it is in line with other researchers' findings (Feenstra, Kirkeby, Thygesen, Danbjørg, & Kronborg, ). It is of utmost importance that professional prenatal breastfeeding education is given, in particular to expecting first time parents.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Primiparous women are more likely to experience pain during breastfeeding than multiparous women is perhaps not a surprising result, nevertheless it is in line with other researchers' findings (Feenstra, Kirkeby, Thygesen, Danbjørg, & Kronborg, ). It is of utmost importance that professional prenatal breastfeeding education is given, in particular to expecting first time parents.…”
Section: Discussionsupporting
confidence: 90%
“…Almost every second woman who reported pain during breastfeeding had a baby that had been given supplementary feeding sometime during the first 3 days postpartum. When mothers have doubts about whether the baby was satisfied after breastfeeding or not, babies are more often given supplementary feeding (Feenstra et al, ). Supplementary feeding can result in suckling less effective or may result in breast refusal (Newman, ), and when given supplementary feeding during initiating of breastfeeding it has been shown to increase complications such as nipple pain (Cloherty et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this association supported previous studies [34,35], we did not ascertain the reason why it was observed only in multiparas. In general, primiparas experienced more breast complications than multiparas [36], as observed in the present study. Furthermore, breast complications strongly relate to psychological breastfeeding-related stress [37].…”
Section: Discussionsupporting
confidence: 82%
“…This observation suggests that the mother should be supported during this period to prevent and overcome breastfeeding di culties. Higher proportions of breastfeeding problems (40-80%) have been reported during the rst week in developed countries (16)(17)(18). An explanation for this noticeable difference is the fact that breastfeeding is common in Africa; therefore, African women could be positive thinkers towards breastfeeding.…”
Section: Discussionmentioning
confidence: 99%